RENAL CELL CARCINOMA IN CHILDREN: A RARE ENTITY - Gilani, Jawad Akhtar; Iqbal, Muhammad; Khattak, M. Rauf; Shahid, Safoora (Journal of Ayub Medical College Abbottabad, 2011)
We present a 15-years old young child primarily presented to general surgeon for abdominal mass and gross haematuria. His detailed imaging studies and other relevant investigations revealed that it is a case of Paediatric Renal Cell carcinoma (RCC), which was clinically not associated with any of the known malignancies or syndromes. On detailed histo-pathological examination this was reported as a special type of Pediatric RCC not fitting into clear cell, papillary, chromophobic, oncocytoma or collecting duct RCC. Keywords: RCC, VHL, IHC